Monsters, law, crime: explorations in gothic criminology - Picart, Caroline Joan (The Fairleigh Dickinson University Press series in law, culture, and the humanities, 2021)
"Monsters, Law, Crime, composed of essays written by prominent U.S. and international experts in Law, Criminology, Sociology, Anthropology, Communication, and Film explores and updates contemporary discussions of the emergent and evolving fronts of monster theory in relation to cutting-edge research on law and crime, and of a Gothic criminology"--